2012
DOI: 10.4081/idr.2012.e9
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Treatment of HIV-Associated Manifestations in Otolaryngology

Abstract: Almost 30 years after its first description, HIV still remains a global pandemic. The present paper aims to review the current knowledge on the ear, nose and throat (ENT) manifestations of HIV infection, and present the available diagnostic and treatment options. A literature review was conducted in Medline and other available database sources. Information from related books was also included in the data analysis. It is well acknowledged that up to 80% of HIV-infected patients eventually develop ENT manifestat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 61 publications
0
20
1
8
Order By: Relevance
“…Of HIV-infected patients, 80 -100% will present to the ENT clinic with early or late manifestations. [2,7,9,10] Previous studies have shown that oral manifestations are the most frequently presented symptoms, followed by cervical head and neck lymphadenopathy, sinusitis and otitis media. [1,2,9] No study of this nature has been conducted in SA; however, studies encompassing 1 155 patients from 3 developing countries; namely Nigeria (n=89), Iran (n=98) and India (n=968), have been conducted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of HIV-infected patients, 80 -100% will present to the ENT clinic with early or late manifestations. [2,7,9,10] Previous studies have shown that oral manifestations are the most frequently presented symptoms, followed by cervical head and neck lymphadenopathy, sinusitis and otitis media. [1,2,9] No study of this nature has been conducted in SA; however, studies encompassing 1 155 patients from 3 developing countries; namely Nigeria (n=89), Iran (n=98) and India (n=968), have been conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Otitis media ranges from 13 to 40%, closely followed by sensory-neural hearing loss and otitis externa. [7,8] There is lack of local information from SSA and SA regarding the otolaryngological (or ENT) and head and neck manifestations in HIV-infected individuals.…”
mentioning
confidence: 99%
“…These authors also mention that physicians and other healthcare providers need to have a high level of suspicion for atypical pathogens such as Alternaria alternata, Aspergillus, Pseudallescheria boydii Cryptococcus, Candida albicans, Acanthamoeba castellani, Microsporidium , and Legionella pneumophila [39,40]. …”
Section: Screeningmentioning
confidence: 99%
“…Early studies demonstrate that ENT symptoms may result in HIV, are associated with progression as well as treatment failure of HIV [6][7][8][9][10]. Therefore, while ENT symptoms are not diagnostic of HIV, it may suggest infection, and ENT specialists should be equipped with knowledge of ENT manifestations associated with HIV [11].…”
Section: Introductionmentioning
confidence: 99%